A Potential Mechanism Underlying the Therapeutic Effects of Progesterone and Allopregnanolone on Ketamine-Induced Cognitive Deficits - Cao, Ting; Tang, MiMi; Jiang, Pei; Zhang, BiKui; Wu, XiangXin; Chen, Qian; Zeng, CuiRong; Li, NaNa; Zhang, ShuangYang; Cai, HuaLin (Frontiers in Pharmacology, 2021)
Ketamine exposure can model cognitive deficits associated with schizophrenia. Progesterone (PROG) and its active metabolite allopregnanolone (ALLO) have neuroprotective effects and the pathway involving progesterone receptor membrane component 1 (PGRMC1), epidermal growth factor receptor (EGFR), glucagon-like peptide-1 receptor (GLP-1R), phosphatidylinositol 3 kinase (PI3K), and protein kinase B (Akt) appears to play a key role in their neuroprotection. The present study aimed to investigate the effects of PROG (8,16 mg kg-1) and ALLO (8,16 mg kg-1) on the reversal of cognitive deficits induced by ketamine (20 mg kg-1) via the PGRMC1 pathway in rat brains, including hippocampus and prefrontal cortex (PFC). Cognitive performance was evaluated by Morris water maze (MWM) test. Western blot and real-time quantitative polymerase chain reaction were utilized to assess the expression changes of protein and mRNA. Additionally, concentrations of PROG and ALLO in plasma, hippocampus and PFC were measured by a liquid chromatography-tandem mass spectrometry method. We demonstrated that PROG or ALLO could reverse the impaired spatial learning and memory abilities induced by ketamine, accompanied with the upregulation of PGRMC1/EGFR/GLP-1R/PI3K/Akt pathway. Additionally, the coadministration of AG205 abolished their neuroprotective effects and induced cognitive deficits similar with ketamine. More importantly, PORG concentrations were markedly elevated in PROG -treated groups in hippocampus, PFC and plasma, so as for ALLO concentrations in ALLO-treated groups. Interestingly, ALLO (16 mg kg-1) significantly increased the levels of PROG. These findings suggest that PROG can exert its neuroprotective effects via activating the PGRMC1/EGFR/GLP-1R/PI3K/Akt pathway in the brain, whereas ALLO also restores cognitive deficits partially via increasing the level of PROG in the brain to activate the PGRMC1 pathway.